Antibacterial Activities of Red Mangrove (Rhizophora stylosa Griff.) Leaf Extract against Klebsiella pneumoniae ATCC 700603 - Kalasuba, Karina; Rahayuningsih, Sri Rejeki; Amalia, Eri; Syaputri, Yolani; Doni, Febri; Rustama, Mia Miranti (Bogor Agricultural University, Indonesia, 2025)
Multidrug-resistant (MDR) Klebsiella pneumoniaeis a critical pathogen causing severe human diseases, including pneumonia. Combating the growing threat of MDRK. pneumoniae requires innovative approaches, such as exploring plant-derived antibacterial agents. Rhizophora stylosa Griff., a mangrove species with traditional medicinal uses, is recognized for its bioactive compounds with potential antibacterial properties. However, research on its bioactive constituents remains limited. This study investigated the antibacterial activity of R. stylosa leaf extracts prepared via maceration and liquid-liquid fractionation against K. pneumoniae ATCC 700603. Using agar-well diffusion and cell leakage assays, the water fraction demonstrated moderate inhibition of K. pneumoniae, producing an average inhibition zone of 8.24 mm and a minimum inhibitory concentration (MIC) of 400 mg/ml. UV-Vis spectrophotometry revealed that the water fraction disrupted protein and nucleic acid synthesis, evidenced by leakage of cellular materials at 260 and 280 nm. Additionally, scanning electron microscopy (SEM) images of K. pneumoniae cells treated with the water fraction showed pore formation and structural damage. These results emphasize the antibacterial potential of the water fraction of R. stylosa leaves against MDRK. pneumoniae. Further investigations are necessary to isolate and identify the specific bioactive compounds responsible for these effects. Moreover, comprehensive assessments of activity and toxicity are crucial to advance R. stylosa-based antibacterial agents as promising alternatives for addressing the challenge of MDR bacterial infections.